Reducing the incidence of overweight and obesity by a healthy lifestyle intervention program for schoolchildren in Hanoi, Vietnam: a randomized controlled trial - Thuy Thi Phuong Pham; Thanh Van Do; Yumi Matsushita; Mitsuhiko Hara; Mai Thi Hoa Tran; Hung Xuan Le; Thanh Thi The Nguyen; Uyen Thu Hoang; Quyen Huyen Dao; Lien Thi Kim Dinh; Hung Phan; Hiroshi Kajio (BMC, 2024)
Abstract Background The increasing incidence and prevalence of childhood overweight (OW) and obesity (OB) are major global health challenges. This study aimed to evaluate the effectiveness of a 2-year healthy lifestyle intervention program in reducing the incidence of OW and OB among schoolchildren aged 11-12 years in Vietnam. Methods Study design: Randomized controlled trial. Participants and interventions: In total, 733 students participated in this study. Participants were included from four schools in Hanoi based on a random cluster sampling method. Students' health outcomes were assessed at baseline and after 2 years. Main outcomes: The primary outcomes were the incidence of OW and OB, and the secondary outcomes were the prevalence and remission of OW and OB. Generalized estimating equations (GEEs) were used to determine the outcomes and risk factors. Results After the intervention, the prevalence of OW decreased by 9.24% in the intervention group and 3.01% in the control group. After adjustment for age and sex, the odds of overweight were 36.7% lower in the intervention group than in the control group (OR = 0.633; 95% CI: 0.434-0.925; P = 0.018). The incidence of OW was 1.31% in the intervention group compared with 5.33% in the control group. After adjustment for age and sex, the odds of incident overweight in the intervention group were 77.4% lower than in the control group (OR = 0.226; 95% CI: 0.063-0.813; P = 0.023). The proportion of patients who achieved OW remission was 41.22% in the intervention group and 28.68% in the control group. After adjustment for age and sex, the odds of OW remission of overweight were 2.219 times greater in the intervention group than in the control group (OR = 2.219; 95% CI: 1.220-4.036; P = 0.009). For most OB-related factors, there were no significant differences between the intervention and control groups. Conclusion A multicomponent healthy lifestyle intervention was effective in reducing the incidence of OW; however, it had no significant effect on OB among children aged 11-12 years in Hanoi, Vietnam. Trial registration Retrospectively registered number: UMIN000014992, 20/08/2023.